1997
DOI: 10.1037/0882-7974.12.4.684
|View full text |Cite
|
Sign up to set email alerts
|

Everyday problem solving across the adult life span: Influence of domain specificity and cognitive appraisal.

Abstract: This study introduces an attributional processing approach to study age differences in dispositional attributions. Dispositional attributions made in the context of relationship vignettes were examined among younger and older adults in 2 conditions (immediate and delayed rating conditions). By using a direct assessment of a 2-step process for making dispositional attributions, it was inferred that a spontaneous adjustment stage occurred following an initial characterization stage as a function of age group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
125
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 30 publications
15
125
0
1
Order By: Relevance
“…Touron and Hertzog [2004], for instance, studied age differences in strategy shift in skill acquisition tasks, where the ability to choose the right strategy has been implicated as one of the key features of human cognition [Lemaire, Arnaud, & Lecacheur, 2004]. Results showed age differences in skill acquisition rates, and an inverse relationship between memory load and performance level [for similar results, see Diehl, Willis, & Schaie, 1995;Blanchard-Fields, Chen, & Norris, 1997]. Extensive findings, in multiple domains, have demonstrated that younger adults are faster and more accurate than their older counterparts, and that the gap between the groups diverges even further with increased complexity and cognitive demands.…”
Section: Bounded Rationality Cognition and Older Adults' Decision Mmentioning
confidence: 61%
“…Touron and Hertzog [2004], for instance, studied age differences in strategy shift in skill acquisition tasks, where the ability to choose the right strategy has been implicated as one of the key features of human cognition [Lemaire, Arnaud, & Lecacheur, 2004]. Results showed age differences in skill acquisition rates, and an inverse relationship between memory load and performance level [for similar results, see Diehl, Willis, & Schaie, 1995;Blanchard-Fields, Chen, & Norris, 1997]. Extensive findings, in multiple domains, have demonstrated that younger adults are faster and more accurate than their older counterparts, and that the gap between the groups diverges even further with increased complexity and cognitive demands.…”
Section: Bounded Rationality Cognition and Older Adults' Decision Mmentioning
confidence: 61%
“…For example, Blanchard-Fields and colleagues (Blanchard-Fields, 1994;Blanchard-Fields & Norris, 1994;Blanchard-Fields, Chen, & Norris, 1997) have shown that causal attributions emphasizing the interaction between dispositional and situational factors are more prevalent in mid-life and later adulthood than at earlier ages. Relatedly, Happé, Winner, and Brownell (1998) examined age differences in theory of mind and found that older adults were more likely than younger adults to make appropriate inferences about the behavior of others based on often complex levels of the actors' mental states.…”
Section: Social Expertise?mentioning
confidence: 96%
“…However, age differences vary by emotional salience and domain of the stress. Older adults reported using more passive strategies than younger adults in response to emotionally salient vignettes and interpersonal situations (Blanchard-Fields, Chen, & Norris, 1997;Blanchard-Fields et al, 1995;Watson & BlanchardFields, 1998).…”
Section: Age and Reactivity To Interpersonal Tensionsmentioning
confidence: 99%